PENGEMBANGAN BAHAN AJAR BALAGHOH MA'ANI BERBASIS COMMUNITY LANGUAGE LEARNING DI KELAS XII MA AL-ITTIFAQIAH INDRALAYA: PENDAHULUAN, METODE PENELITIAN. HASIL DAN PEMBAHASAN - Nurhayati, Umi; Hadi, Jumhur; Qaaf, M. Al Fath; Ira Ivanka, Viky; Faisal, Muhammad (SHAWTUL ARAB, 2025)
This study aims to development Balaghoh Ma'ani teaching materials based on Community Language Learning (CLL) for twelfth-grade students Al-Ittifaqiah Indralaya Senior High School to enhance their understanding and engagement in learning. The research employs the Research and Development (R&D) method using the Borg & Gall model, which consists of six main steps: identifying potential and problems, data collection, product design, product validation, revision, and product testing. The developed teaching materials were tested on 21 twelfth-grade students at Al Ittifaqiah Indralaya Senior High School Data were collected through interviews, observations, documentation, questionnaires, and tests in the form of pre-tests and post-tests. The research results indicate that the developed teaching materials received validation scores of 77% from subject matter experts and 80% from media experts, categorizing them as valid. Effectiveness testing showed an improvement in students learning outcomes, with the Paired Sample T-test yielding a significance value of 0.000< 0.05, indicating a significant difference between pre-test and post-test scores. Additionally, the N-Gain Score of 0.58 suggests that the developed teaching materials were moderately effective in enhancing students' comprehension. Thus, the development of Balaghoh Ma'ani teaching materials based on CLL has been proven to improve students' understanding and engagement in learning while addressing the limitations of conventional, non-interactive teaching materials.